Effect of different milking methods on total plate count and somatic cell count - Yazed, Nurul Asyikin (2016)
Cow milk is one of the human diets that rich in nutrient components which composed of about 86-88% water, 3.5% of protein, 3% to 4% of milk fat, 5% of lactose and 0.7% minerals depending on breeds, animal’s feeding and stage of lactation as well (FAO, 2015). The TPC and SCC are two of the indicators of milk quality (Pasteurized Milk Ordinance, 2011). The objectives of this study were to evaluate, compare and test the correlation of total plate count (TPC) and somatic cell count (SCC) level in milk collected from different milking methods. This study was conducted at Milk Quality Control Laboratory, Alor Gajah Melaka and UPM laboratories. Nine dairy farms from Merlimau, Alor Gajah and Linggi were involved in this study. Milk samples were collected from 103 individual healthy Friesian and Jersey cows, which 36 of them collected samples were collected from line machine milking, 40 samples from portable machine milking and 27 samples from hand milking. Milk samples were analysed for TPC, milk compositions and SCC. Based on the analysis of TPC (log) result, the highest total plate count were significantly lower (P<0.05) in milk collected from cows using line milking machine compared to portable milking machine, but no different (P>0.05) compared to hand milking. There were no significant different (P>0.05) in the somatic cell count and milk compositions reported in the milk collected from portable machine milking, hand milking or machine milking. In conclusion, milk collected from cows milked using line machine milking had the lowest number of bacteria when compared to hand milking and portable milking machine, but no different on the number of somatic cells in the milk or milk composition. There are minor relationship between total plate count and somatic cells count.